2015
DOI: 10.1186/s13256-015-0549-0
|View full text |Cite
|
Sign up to set email alerts
|

Pancraniosynostosis following endoscopic-assisted strip craniectomy for sagittal suture craniosynostosis in the setting of poor compliance with follow-up: a case report

Abstract: IntroductionThere is limited craniofacial literature on the complications of helmet therapy and controversy regarding the effects of inadequate orthotic helmet therapy. The authors present a case of inadvertently prolonged orthotic helmet therapy after endoscopic strip craniectomy for isolated sagittal synostosis.Case presentationA two-month-old Caucasian baby underwent uncomplicated endoscopic-assisted strip craniectomy to treat synostosis of the sagittal suture and was fitted for an orthotic helmet two weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…This explains the observation that older infants with sagittal synostosis present with a smaller anterior fontanelle. An interesting notion to consider is the phenomenon of delayed synostosis of uninvolved sutures or even pansynostosis (premature fusion of all sutures) after surgical intervention (Greene, 1998;Jenkins et al 2013;Yarbrough et al 2014;Sivakumar et al 2015). With our findings indicating a tendency to early closure at metopic and coronal sutures in the sagittal synostosis cohort, it is worthwhile to investigate the effects of the surgery and the synostosis on the uninvolved sutures separately.…”
Section: Premature Closure Of Uninvolved Suturesmentioning
confidence: 83%
See 2 more Smart Citations
“…This explains the observation that older infants with sagittal synostosis present with a smaller anterior fontanelle. An interesting notion to consider is the phenomenon of delayed synostosis of uninvolved sutures or even pansynostosis (premature fusion of all sutures) after surgical intervention (Greene, 1998;Jenkins et al 2013;Yarbrough et al 2014;Sivakumar et al 2015). With our findings indicating a tendency to early closure at metopic and coronal sutures in the sagittal synostosis cohort, it is worthwhile to investigate the effects of the surgery and the synostosis on the uninvolved sutures separately.…”
Section: Premature Closure Of Uninvolved Suturesmentioning
confidence: 83%
“…; Sivakumar et al. ). With our findings indicating a tendency to early closure at metopic and coronal sutures in the sagittal synostosis cohort, it is worthwhile to investigate the effects of the surgery and the synostosis on the uninvolved sutures separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while Kim et al 9 suggested visible head deformity was the most common presenting sign for diagnosis, our study found radiologic imaging to be the most common method of diagnosing idiopathic secondary stenosis. Often it was described on radiology in the literature as “closed sutures”, “copper beaten”, “thumb printing”, or “scalloping” 2,8,11–16 . In almost all recorded cases in the literature, the radiographic method employed was x-ray, although Jenkins et al 17 described using computed tomography to show their patient having pansynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…These materials include polyethylene films, pericranial grafts, interpositioned biodegradable polyglycolic acid (PGA) membrane, interposed silicon membrane or expanded polytet-█ INTRODUCTION A chievement of re-ossification is the main goal of treatment in most clinical conditions with bone defects, especially in bone surgery. However, the prevention of new bone formation is critical in certain clinical settings, such as premature epiphyseal fusion of long bones (10,11), and after the craniosynostosis surgery (5,14,16).…”
mentioning
confidence: 99%